Laparoscopic Appendectomy in Children: Tunisian Experience - Hayet Zitouni; Najoua Ben Kraiem; Saloua Ammar; Mahdi Ben Dhaou; Riadh Mhiri (Turkish Archives of Pediatrics)
Objective: The purpose of this study is to compare the surgical outcomes of open appendectomy (OA) and laparoscopic appendectomy (LA) for pediatric acute appendicitis in order to guide its future management.